Perbandingan Metode TOPSIS Dan SAW Dalam Penentuan Guru Berprestasi - TITIN PRIHATIN (JURNAL TEKNIK KOMPUTER, 2019)
- Determination of outstanding teachers at Pondok Duta Islamic Middle School has been applied every year. This process is very important to improve the quality of human resources in the progress of Pondok Duta Islamic Middle School. In its implementation, the determination of teachers with pretensions is still considered subjective, because it is only based on personal opinions and is not based on certain criteria. The Simple Additive Weighting (SAW) method is often known as the weighted sum method. The basic concept of the method of Simple Additive Weighting (SAW) is to find a weighted sum of performance ratings on each alternative on all attributes. While the Technique for Order Performance of Similarity to Ideal Solution (TOPSIS) method uses the principle that the chosen alternative must have the longest (farthest) distance from the negative ideal solution from a geometric point of view using the relative proximity of an alternative. The two methods, namely the Technique for Order Performance of Similarity to Ideal Solution (TOPSIS) method and the Simple Additive Weighting (SAW) method can help in the process of determining the teacher to be prescribed who recommend results based on the main criteria that have been determined.